How does forgiveness therapy versus emotion-focused therapy reduce violent behavior schizophrenia post restrain at East Java, Indonesia? - Muhammad Suhron; Ah. Yusuf; Rika Subarniati; Faisal Amir; Zakkiyatus Zainiyah (International Journal of Public Health Science (IJPHS), 2020)
Based on the violent behavior, the data obtained in the last 6 months using population of psychiatric inpatients with violent behavior of 64 patients. The purpose of this study was to analyze the effect of forgiveness therapy that focused on emotions of violent behavior in post restrain schizophrenia. This research method used a Quasi-experimental design. The independent variable was forgiveness therapy that focused on emotions. The dependent variable was violent behavior. The populations were 64 patients with violent behavior using a simple random sampling technique and for the sample were 52 patients. Collecting data using general adaptive function response score (GAFR) observation sheets with Wilcoxon and Mann Whitney statistical tests. Wilcoxon test showed (p-value 0.002) after being given forgiveness therapy. The Wilcoxon test showed (p-value 0.513) after being given therapy that focused on emotions it can be concluded that there are differences in violent behavior before and after therapy of forgiveness and therapy that focused on emotions. Mann Whitney test results obtained (p-value 0.016) remission therapy was more effective in reducing the violent behavior of post restrain schizophrenia.